Zastosowanie improwizacji grupowych i indywidualnych w kształtowaniu zdrowia psychicznego i rozwijania zdolności psychologicznych u uzdolnionej artystycznie młodzieży = The use of group and individual improvisations in shaping mental health and developing psychological abilities in artistically talented youth - Kaczmarek, Stella (Kraków ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
Most often, music therapy for clinical purposes is used to improve well-being, reduce pain and anxiety, reduce stress or trauma. In music education, on the other hand, it can be used to improve concentration, motivation and support the child?s creativity. Especially group and individual improvisations, informal or structured, can be used in music (and artistic) education as a means and form supporting the psyche of a young person.
Keywords: szkolnictwo artystyczne; muzykoterapia; improwizacje; młodzież; wspomaganie zdrowia; artistic education; music therapy; improvisations; youth; health support